The characteristics of starch gels molded by 3D printing. Issue 7 (8th May 2019) - Zheng, Luyao; Yu, Yangling; Tong, Zhaobin; Zou, Qianhui; Han, Shiyao; Jiang, Hao
Abstract: As an emerging processing method, 3D printing attracts more attention on food manufacturing. The characteristics of 3D printed samples made from potato, wheat, and corn starch were investigated in this study. Morphology, color, iodine absorption spectra, rapid visco analyzer, texture analysis, Fourier transform infrared spectroscopy and scanning electron microscopy were used to evaluate the quality of products. The results indicated that all starch gels could obtain a complete 3D printing model. The dimension of 3D printed sample created by wheat starch was closest to the CAD designed model. Wheat starch gel displayed the lowest viscosity and better extrudability as well as better storage properties. Besides, the microstructure of 3D printed samples processed by wheat starch presented more regular network structure than potato and corn starch. The study provides a new theory for the application of 3D printing in food production and technical support for actual production. Practical applications: 3D printing also referred to as additive manufacturing, offers a wide range of new processing possibilities to the food industry. It potentially allows rapid manufacturing of complex objects, which are unhindered by design complexity, thus providing substantial liberty to create new and untested geometric shapes. In terms of food manufacturing, the potential that 3D food printing technologies can bring may revolutionize certain aspects of food manufacturing, providing the convenience of low‐cost customized fabrication and even tailored nutrition control. Be an emerging food processing method, it is important to develop more compatible materials. Starch is a polymeric carbohydrate composed of a large number of glucose units connected by glyosidic bonds. It is also the most abundant source of carbohydrate in human diet. Using starch as the 3D food printing material can be a good choice with good mechanical behaviors and lower cost.